Analysis of the Implementation of Infection Prevention and Control (PCU) Program in the Inpatient Room - Sri Lestari Ramadhani Nasution; Febby Maulina; Ermi Girsang (Postgraduate, University of Mataram, 2023)
This study aims to analyze the application of the infection prevention and control program (PCU) in the inpatient room of the Meuraxa Regional General Hospital, Banda Aceh City. This research is an observational analytic study with a cross-sectional approach with a total sample of 184 respondents who are permanent nurses in the inpatient room of the Meuraxa Regional General Hospital, Banda Aceh City. This study used primary data through distributing questionnaires which were conducted in July 2023. Correlation analysis used statistical contingency coefficient tests and Multiple Logistic Regression tests on multivariate variables. The results showed that gender (p=0.033), age (p=0.004), and length of work (p=0.024) had a correlationwith the implementation of the PCU program in the inpatient room.The Multiple Logistic Regression Test showed that the implementation of the PCU program was 2.79 times higher for female respondents and2.37 times higher implemented at age26 - 35 years. This study shows that gender, age, and length of work have a significant correlationby implementing an infection prevention and control program (PCU) in the inpatient room of the Meuraxa Regional General Hospital, Banda Aceh City.